The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.22456/1982-6524.88858
|View full text |Cite
|
Sign up to set email alerts
|

Agroecologia Em Terras Indígenas No Brasil: Uma Revisão Bibliográfica

Abstract: Este texto apresenta um estudo de revisão bibliográfica sobre as atividades realizadas com base na noção de Agroecologia em terras indígenas de diferentes regiões brasileiras. Foram identificadas 92 publicações que retratam iniciativas e projetos envolvendo diversas em terras indígenas, etnias e instituições. Esta produção acadêmica foi analisada a partir de uma classificação em sete temas: práticas agrícolas; agrobiodiversidade; sistemas agroflorestais; manejo florestal e extrativismo; organização social e po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The increase in local density is one of the reasons for reducing the fallow time. The negative impacts of this more intense use of the land, according to Norder et al (2019), include lower soil fertility and reduced cultivation of some plants, such as rice and other cultivars.…”
Section: Characterization Of the Analyzed Workmentioning
confidence: 99%
“…The increase in local density is one of the reasons for reducing the fallow time. The negative impacts of this more intense use of the land, according to Norder et al (2019), include lower soil fertility and reduced cultivation of some plants, such as rice and other cultivars.…”
Section: Characterization Of the Analyzed Workmentioning
confidence: 99%
“…Respecting the specificities of each group, the initiatives aimed to create sustainable and adapted productive systems, sustainable forest management and the formation of agroforestry systems. Mainly, this refers to the adoption of participatory and dialogic methods, aimed at empowering communities, reflection on gender relations, youth, the improvement of eating habits and environmental management, with reorientation in the fields of education and extension (NORDER et al, 2019).…”
Section: Lessons For Extension Services and Development Projects In T...mentioning
confidence: 99%
“…Several reported initiatives have operated based on field days, on-farm demonstrations of restoration of degraded areas, hands-on management of agroforestry systems, seed exchange fairs, incentives for and protection of cultural expressions, etc. (NORDER et al, 2019;CAMPOS;GODOY;SILVA, 2018;QUEIROZ, 2013). Potentially, indigenous community members may benefit from these initiatives, by appropriating knowledge, strengthening local capacities and obtaining some advantage (PORTER, 1985), associated with fostering rural enterprises or enhancing food security and food sovereignty (MARKHAM; KERINS, 2020;ROGERS et al, 2018).…”
Section: Lessons For Extension Services and Development Projects In T...mentioning
confidence: 99%
“…Agricultural practices developed by Indigenous peoples are not only considered management techniques, but also part of their lifestyle, traditions, spirituality, and religious beliefs (14). For example, the Mbyá people, from the Yryapu Indigenous lands, in the municipality of Palmares, Rio Grande do Sul, grow a wide variety of foods, such as cassava, beans, corn, watermelon, and others (14). The fact that several associated cultures coexist prevents soil depletion.…”
Section: Agricultural Practicesmentioning
confidence: 99%
“…The fact that several associated cultures coexist prevents soil depletion. Furthermore, Norder et al (14) have indicated that the preservation of forests has been identified as essential for the cultural, social, and religious traditions of Indigenous peoples, and low-impact techniques demonstrate the extent to which soil is essential for food production. Therefore, these practices make the relationship between agriculture and the environment harmonious in Indigenous society.…”
Section: Agricultural Practicesmentioning
confidence: 99%